Kinetics of reduction of Banded Haematite Jasper ore with coal. Issue 2 (3rd April 2021) - Das, Sanjeev Kumar; Prasad, Ranjit; Singh, Rajendra Prasad; Ranganathan, Srinivasan
ABSTRACT: The kinetics of reduction of Banded Haematite Jasper ore with commercial coal was investigated in the temperature range 1273–1473 K. At 1273 and 1373 K, the degree of reduction was low. It increased four folds at 1473 K compared to the reduction at lower temperatures. Silicon carbide, SiC, was formed as the predominant phase during reduction at 1273–1373 K. This hindered the reduction of iron oxide in the ore. This phase is not stable at temperatures above 1473 K. Absence of this phase accelerated the reduction of iron oxide at higher temperatures. At 1273 K, reduction was controlled by chemical reaction kinetics. At higher temperature, it was controlled by diffusion. The activation energy for reduction at higher temperatures was 601 kJ/mol. This indicates that reduction was controlled by the Bouduoard reaction. The relatively high temperature required for the reduction of iron oxide in the ore is an important feature that should be taken into consideration when designing processes for the exploitation of this as a source of iron.